(untitled) (IAHS Medical Journal, 2024)
Background: Postpartum anemia is a leading cause of maternal mortality and morbidity throughout the world, particularly in developing countries.The most common causes of postpartum anemia are antepartum iron deficiency anemia and blood loss during childbirth. Treatment of anemia with ferric carboxymaltose during labor can considerably reduce maternal and newborn morbidity. The aim of the study is to compare the effectiveness of iron sucrose and ferric carboxymaltose in the treatment of postpartum anaemia following caesarian section. Materials and methods: A comparative cross-sectional study was carried out among the 234 outdoor patients of the Department of Obstetrics and Gynecology at Sheikh Hasina Medical College Hospital, Tangail during the period from July 2017 to June 2020. Results: The pre-transfusion mean of hemoglobin level was 8.9±0.5 gm/dl and the post-transfusion mean of hemoglobin level was 10.4±0.4 gm/dl in group A. The pre-transfusion mean of hemoglobin level was 8.7±0.7 gm/dl and the post-transfusion mean of hemoglobin level was 11.0±0.4 gm/dl in group B. The mean of increased hemoglobin level was 1.5±0.4 gm/dl and 2.3±0.5 gm/dl respectively in both groups. The pre-transfusion mean of ferritin level was 46.3±16.1 ng/mL and the post-transfusion mean of ferritin level was 171.5±25.8 ng/mLin group A. The pre-transfusion level was 46.5±16.2 ng/mL and the post-transfusion mean ferritin level was ±24.9 ng/mLin group B. The mean of increased ferritin level was 125.2±22.2 ng/mL and 149.0± 20.5 ng/mL respectively in both groups. These differences were statistically significant within the study groups (p<0.05). Conclusions: The study revealed that serum ferritin levels increased significantly in the FCC group than ISC group. Ferric carboxymaltose are more effective and safe for the treatment of iron deficiency anemia in postpartum patients. IAHS Medical Journal Vol 7(1), June 2024; 8-12